2016
DOI: 10.1007/s11250-016-1190-7
|View full text |Cite
|
Sign up to set email alerts
|

Selective, reliable blood and milk bio-markers for diagnosing clinical and subclinical bovine mastitis

Abstract: Mastitis is positioned as the most vital ailment in dairy cows in light of conventional cost examinations. The aim of the present study was to evaluate the diagnostic value of different acute phase proteins (APPs), pro-inflammatory cytokines, and oxidative stress biomarkers in healthy cows and in those with clinical or subclinical mastitis and to localize APP gene expression in the milk of mastitic cows. Therefore, 20 subclinical mastitic cows with positive California Mastitis Test (CMT) results and no clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 17 publications
3
33
0
4
Order By: Relevance
“…Alterations in the serum level of cytokines, the key mediators of inflammation and immune-mediated diseases, have been found to be closely associated with various diseases. For example, significantly elevated serum levels of cytokines were observed in bovine with clinical and subclinical mastitis (including interleukin (IL)-1, IL-2, IL-6, and tumor necrosis factor-alpha) (Sadek et al 2017) as well as in rabbits infected with Mycobacterium tuberculosis (including vascular endothelial growth factor, platelet derived growth factor, IL-17A, and IL-18) (Dehnad et al 2016). Significant down-regulation of serum IL-7 was identified in acute human cholangitis (Suwa et al 2017), and substantial increase in plasma IL-6 level was observed in mice infected with influenza A virus (Chockalingam et al 2016) as well as in human patients infected with Trypanosoma brucei rhodesiense (Kato et al 2015).…”
mentioning
confidence: 99%
“…Alterations in the serum level of cytokines, the key mediators of inflammation and immune-mediated diseases, have been found to be closely associated with various diseases. For example, significantly elevated serum levels of cytokines were observed in bovine with clinical and subclinical mastitis (including interleukin (IL)-1, IL-2, IL-6, and tumor necrosis factor-alpha) (Sadek et al 2017) as well as in rabbits infected with Mycobacterium tuberculosis (including vascular endothelial growth factor, platelet derived growth factor, IL-17A, and IL-18) (Dehnad et al 2016). Significant down-regulation of serum IL-7 was identified in acute human cholangitis (Suwa et al 2017), and substantial increase in plasma IL-6 level was observed in mice infected with influenza A virus (Chockalingam et al 2016) as well as in human patients infected with Trypanosoma brucei rhodesiense (Kato et al 2015).…”
mentioning
confidence: 99%
“…Wellnitz et al (2016) found that pathogens such as E. coli had a great effect on the blood-milk barrier and a large amount of blood proteins were transferred into milk. Serum albumin has been suggested as a marker for infection and for estimating transfer of proteins implicated in the udder defense (Tothova et al, 2014;Wall et al, 2015;Sadek et al, 2017). Decreased blood WBC, NEU, LYM, TP, ALB, and GLOB observed in our study ( Figure 5) may be attributed to the increased permeability of the bloodmilk barrier in the udder of goats challenged with LPS.…”
Section: Discussionmentioning
confidence: 56%
“…The evaluation of diagnostic biomarkers of SCM has attracted great attention in recent years. A large amount of evidence indicates that some inflammatory markers, such as bovine serum albumin, haptoglobin, N-acetyl-β-dglucosaminidase, lactate dehydrogenase, serum amyloid protein or S100A12, are potential markers to detect cows with inflammation yet to be demonstrated (Chagunda, Friggens, Rasmussen, & Larsen, 2006;He et al, 2015;Sadek, Saleh, & Ayoub, 2017).…”
Section: Discussionmentioning
confidence: 99%